2022
DOI: 10.3390/children9060917
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Echocardiographic Analysis in Medium-Term Follow-Up of Children with Previous Multisystem Inflammatory Syndrome

Abstract: Multisystem inflammatory syndrome in children (MIS-C) is a severe hyperinflammatory disease related to SARS-CoV2 infection, with frequent cardiovascular involvement in the acute setting. The aim of the study was to evaluate the cardiac function at 6 months. Thirty-two patients diagnosed with MIS-C were enrolled and underwent advanced echocardiogram at discharge and at 6 months. According to the left ventricular ejection fraction (LVEF) at admission, the patients were divided into group A (LVEF < 45%) and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 42 publications
(60 reference statements)
2
16
0
Order By: Relevance
“…Notably, in our group of patients, while there was a trend for improvement in LV-GLS measurements, it was not statistically signi cant, probably due to the small sample size. Our ndings are consistent with those reported by other studies, that observed a normalization of the LV-GLS in the majority of MIS-C patients at a six-month follow-up, where the rates of participants with residual GLS impairment ranged from 0 to 13% [11,12,18].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Notably, in our group of patients, while there was a trend for improvement in LV-GLS measurements, it was not statistically signi cant, probably due to the small sample size. Our ndings are consistent with those reported by other studies, that observed a normalization of the LV-GLS in the majority of MIS-C patients at a six-month follow-up, where the rates of participants with residual GLS impairment ranged from 0 to 13% [11,12,18].…”
Section: Discussionsupporting
confidence: 93%
“…In previous reports, decreased LVEF was more common, as it was present, during the acute illness, in 34.2-40% of children with MIS-C [14,16,35]. In line with the ndings of previous studies, that described a rapid improvement of LVEF, returning to normal by the rst days to weeks from admission, all the participants of our cohort, had preserved LVEF on follow-up [12,13].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There were 206 publications that resulted with our keyword search on MIS-C and follow-up between 2020 and 2022. Eleven published studies fit the inclusion criteria with a total of 343 participants (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). All studies included patients who met criteria for MIS-C per the CDC guidelines (see Figure 1).…”
Section: Yield Of the Searchmentioning
confidence: 99%